Análisis comparativo de las publicaciones en noticias del diario la hora de Loja, con respecto a la censura de contenido violento estipulado en la ley orgánica de comunicación 2013, entre los períodos 1997/1998 y 2013/2014. - Morocho Sanmartin, Miguel Angel (2019)
The media of today in our country (Ecuador), must be governed by the statutes of the Ley Orgánica de Comunicación, which together with the regulatory bodies controls the type of content and emission within them, likewise the type of sanction according to his infraction. The newspaper "La Hora" is an exponent nationwide that has been characterized by the publications issued in the different regions of the country, however, it is one of the means that has had to be coupled to the dictated within the law, therefore, one of the goals of this project is to determine if in this newspaper there has been some type of modification in its publication format and the incidence from the official launching of said law. The most appropriate way to study these differences and modifications is to use the observation forms, which will ratify an investigative involvement with the field of study, together with the interviews, which will allow obtaining the necessary answers and determining the conclusions according to the data obtained. The publications that years ago made the printed media "La Hora", exhibited much more violent content, unlike the year 2013 on, however despite the release of the Ley Orgánica de Comunicación in that same year you could still see news of This type, even carried out advertising of animal violence, such as the well-known bullfights, however, this newspaper has modified its way of dealing with this information, so it has reorganized its publications in a more orderly manner, that is, by specific sections. Based on these results, it is proposed to develop a seminar-workshop to train students of the Social Communication Career at the National University of Loja, about printed publications with violent content in the current media, creating a culture of journalistic awareness through ethics and social responsibility.